Comparison of selenium-mediated regulation of heat shock protein and inflammation in-vitro and in-ovo for heat resistance enhancement in broiler - Junseok Ban; Jonghyun Jung; Kwanseob Shim; Darae Kang (Poultry Science)
ABSTRACT: Selenium is a heat-stress-reducing substance that improves heat resistance and is being studied for its effective application in the broiler industry. However, research on feed additives is labor-intensive and time-consuming because of the need for feeding experiments. We aimed to compare the effects of selenium under heat stress in vitro and in ovo, specifically examining the gene expression of heat shock proteins (HSP) and inflammatory markers. Two groups were included in the in-vitro study: in-vitro control (TC; selenium 0 μg/ml) and in-vitro selenium (TS; selenium 5 μg/ml). The satellite cells were cultured at 42°C for 48 h after selenium treatment. The in-ovo study comprised 4 groups: in-ovo control and in-ovo selenium 1-3 (OC, OS1, OS2, and OS3; selenium 2.5, 5, and 10 μg/egg, respectively). Selenium was injected on the 18th day after hatching, and heat treatment was performed at 32–34°C from the 14th to the 21st day after hatching, and the leg muscles of the chicks were collected on the 21st day. The gene expression of heat shock proteins (HSP), caspase3, nuclear factor kappa light-chain enhancer of activated B cells (NF-kB), and IL-8 was analyzed in in-vitro and in-ovo experiments, respectively. In-vitro results showed significant increases in HSP90, HSP60, and HSP40 in TS compared to TC, with a significant decrease in HSP70. In the in-ovo study, HSP70, caspase3, NF-kB and IL-8 were significantly increased in OS1. HSP90, HSP60, HSP40, HSP27 and NF-kB were significantly decreased in in-ovo OS2 compared to in-vitro TS, implying a trend in ratio compared to control. Selenium appeared to enhance heat resistance in-vitro and in-ovo by modulating HSPs and inflammation. However, differences in mRNA expression were observed depending on the concentration of selenium. These findings suggest that selenium modulates heat resistance through different mechanisms in-vitro and in-ovo, likely due to the complexity of whole-organism interactions in-ovo compared to the single-cell-type environment in-vitro. Therefore, to directly apply in-vitro results to in-ovo, a concentration comparison study for each additive is necessary.